2012
DOI: 10.1089/neu.2011.1923
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous GFAP-Positive Neural Stem/Progenitor Cells in the Postnatal Mouse Cortex Are Activated following Traumatic Brain Injury

Abstract: Interest in promoting regeneration of the injured nervous system has recently turned toward the use of endogenous stem cells. Elucidating cues involved in driving these precursor cells out of quiescence following injury, and the signals that drive them toward neuronal and glial lineages, will help to harness these cells for repair. Using a biomechanically validated in vitro organotypic stretch injury model, cortico-hippocampal slices from postnatal mice were cultured and a stretch injury equivalent to a severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 78 publications
1
32
0
Order By: Relevance
“…These GFAP+ astrocytes exhibited a hypertrophic morphology comparable to glial scars that form subsequent to traumatic brain injury. Because glial scars are normally associated with neural trauma [25], we asked if the GFAP+ cells that accumulated in and around tumor tissues were also scar-like and contained proliferative astrocytes. We found 20 % of the GFAP+ cell population in the peritumoral brain region co-express the proliferative marker Ki67; with 30 % of these Ki67+/GFAP+ proliferative astrocytes appearing to have infiltrated at the tumor edge (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These GFAP+ astrocytes exhibited a hypertrophic morphology comparable to glial scars that form subsequent to traumatic brain injury. Because glial scars are normally associated with neural trauma [25], we asked if the GFAP+ cells that accumulated in and around tumor tissues were also scar-like and contained proliferative astrocytes. We found 20 % of the GFAP+ cell population in the peritumoral brain region co-express the proliferative marker Ki67; with 30 % of these Ki67+/GFAP+ proliferative astrocytes appearing to have infiltrated at the tumor edge (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These physiological processes are accentuated near sites of traumatic brain injury, and ischemia, suggesting a role for NPCs and their differentiated descendants in pathological responses. [25, 46]. Thus, although migratory NPCs are known to exist in the post-natal mammalian brain, little is known about any molecular cues mediating their activation, migration, and differentiation in during brain metastasis [47].…”
Section: Discussionmentioning
confidence: 99%
“…So many survival head-injured patients were long-term disability for permanent neurological impairment. The economic and health burden of TBI is significant and is predicted to grow further in the next decade [6], [7].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, unlike the formation of the astrocytic glial scar in vivo , isolation of the cells in vitro removed the influence of the injury microenvironment. To demonstrate that the injury-activated cell has the capacity to behave as an NSC outside of the injury milieu, Buffo et al 7 showed that mature astrocytes that had been isolated from the injured cerebral cortex acquired NSC-like properties in vitro through a processed termed ‘dedifferentiation’ and has also demonstrated this using an organotypic model 28. Therefore, while there are cells resident in the cortex as well as cells migrating into the injured cortex that display properties of NSCs, the injury environment prevents them from following a neurogenic fate.…”
Section: Endogenous Nscs and Tbimentioning
confidence: 99%